Vitamin D deficiency in athletes: Laboratory, clinical and field integration - Tina Shuk-Tin Ip; Sai-Chuen Fu; Michael Tim-Yun Ong; Patrick Shu-Hang Yung (Elsevier, 2022)
Vitamin D deficiency is highly prevalent in athletes. Increased utilisation and storage depletion may be key contributing factor. We found a higher prevalence of vitamin D inadequacy (deficiency/ insufficiency) in power than endurance sport athletes, which may be related to vitamin D utilisation and reserve in skeletal muscles.